A 2‐year prospective clinical and bone density evaluation, with a subset undergoing radiostereometric analysis, using the Absolut cemented stem. Issue 4 (2nd February 2022) - Ebert, Jay R.; Nivbrant, Nils O.; Petrov, Victoria; Yates, Piers; Wood, David J.
Abstract: Background: Total hip arthroplasty (THA) is common though the investigation of new prostheses requires a practical, step‐wise introduction. This study reports the 2‐year clinical results and periprosthetic bone mineral density (BMD) changes, along with a subset undergoing Radiostereometric analysis (RSA), in patients undergoing primary cemented THA using a new highly polished, double tapered, collarless femoral stem (Absolut). Methods: Between August 2013 and December 2016, 47 patients with a mean age of 74.2 years (range 36–89) underwent 51 THAs with the Absolut. All patients underwent clinical assessment pre‐surgery and at 6 weeks, 3, 12 and 24 months using the Oxford and Harris Hip Scores, as well as Dual Energy X‐ray Absorptiometry (DEXA) to assess BMD within 2–4 weeks post‐surgery, 12 and 24 months. RSA was undertaken in a patient subset (the first n  = 30) early post‐surgery (1–2 days) and 3, 12 and 24 months. Results: All clinical scores significantly improved ( p  < 0.05). RSA revealed a mean subsidence of 0.78 mm at 3 months, 1.23 mm at 12 months and 1.51 mm at 24 months. Anterior–posterior and medial‐lateral translation was negligible. A significant increase ( p  = 0.020) in BMD was observed in Gruen zone 1, though no significant changes were observed for any other zone up until 2 years. Two patients acquired an early post‐operative deep vein thrombosis that were treated accordingly and resolved, with no further complications or re‐operations. Conclusion: The Absolut cemented femoral stem demonstrated good outcomes, BMD changes consistent with sound prosthesis integration and patterns of post‐operative micromotion observed in other successful cemented stems. Abstract : Total hip arthroplasty (THA) is common though the investigation of new prostheses requires a practical, step‐wise introduction. In the current study, the Absolut cemented prosthesis, a highly polished, double tapered, collarless femoral stem (Absolut), demonstrated good outcomes, periprosthetic bone mineral density changes consistent with sound prosthesis integration and patterns of post‐operative micromotion observed in other successful cemented stems.